Pengaruh Employee Engagement Terhadap Kepuasan Kerja Pegawai Di Kantor Kedinasan Kejaksaan Tinggi Sumatera Barat - Ariel Dohan; Farhan Alpha Rindika; Muthia Firstry Mayhapdi; Andry Novrianto (CV. ITTC INDONESIA, 2025)
This research aims to determine the influence of Employee Engagement on Employee Job Satisfaction at the West Sumatra High Prosecutor's Office. This research uses a quantitative approach by distributing questionnaires to customers as many as 30 respondents. The data processing technique uses the SMART PLS Version 3.0 computer program, in the form of a validity test,reliability,convergen validity, Algorithm test, Boutstrapping test, and Blindfolding test. The results of this research show that Employee Engagement and Job Satisfaction together have a positive and significant effect on performance. Using the Slovin formula method, a score of 30 respondents was obtained. The implication of this research is that with employee engagement and work satisfaction in the West Sumatra High Prosecutor's Office, employee performance can increase.